Post-translational palmitoylation of metabolic proteins - Dennis, Kaitlyn M. J. H.; Heather, Lisa C. (Frontiers in Physiology, 2023)
Numerous cellular proteins are post-translationally modified by addition of a lipid group to their structure, which dynamically influences the proteome by altering protein function and localization through increased hydrophobicity. These lipid modifications include myristoylation, prenylation and palmitoylation. Palmitoylation involves a C16-carbon saturated fatty acyl chain being covalently linked to a cysteine thiol through a thioester bond. Palmitoylation is unique within this group of modifications, as the addition of the palmitoyl group is reversible and enzyme driven, rapidly affecting protein targeting, stability and subcellular trafficking. The palmitoylation reaction is catalyzed by a large family of Asp-His-His-Cys (DHHCs) motif-containing palmitoyl acyltransferases, while the reverse reaction is catalyzed by acyl-protein thioesterases (APTs), that remove the acyl chain. Palmitoyl-CoA serves as an important dual purpose as it is not only a key metabolite fueling energy metabolism, but is also a substrate for this PTM. In this review, we discuss protein palmitoylation in regulating substrate metabolism, focusing on membrane transport proteins and kinases that participate in substrate uptake into the cell. We then explore the palmitoylation of mitochondrial proteins and the palmitoylation regulatory enzymes, a less explored field for potential lipid metabolic regulation.